1995
DOI: 10.1364/josaa.12.002446
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-nondiffracting beams generated by radial harmonic functions

Abstract: A Fourier hologram with the distribution of a radial harmonic function creates a nondiverging beam in the far field. The properties of this beam are analyzed and the beam is demonstrated. We also give a set of theorems that describe the relations between the hologram and the longitudinal distribution of the beam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…The analogous case to this phenomenon from diffraction theory can be found in Ref. 19. Thus the tilt and the effect of the noncentered zone-plate-like source together can explain the phenomenon that the first order is a peak above all the rest, which we observed in our experiments.…”
Section: B Influence Of Source Misalignmentssupporting
confidence: 86%
“…The analogous case to this phenomenon from diffraction theory can be found in Ref. 19. Thus the tilt and the effect of the noncentered zone-plate-like source together can explain the phenomenon that the first order is a peak above all the rest, which we observed in our experiments.…”
Section: B Influence Of Source Misalignmentssupporting
confidence: 86%
“…Earlier, the propagation of the BB through the optical system was studied in [33][34][35]. In [33] using the ABCD-matrix transform it was shown that, being imaged, the BB changes in scale, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the diverging BB imaged by a spherical lens is also a diverging BB (see equation (21) in [34]). In [35] pseudo non-diffracting light beams were studied, the BB beams being a particular case. It was shown that a hologram of transmittance given by a radial angular harmonic (see equation (5) in [35]) is able to form a converging BB in the neighbourhood of the spherical lens' focal plane (see equation (12) in [35]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7 The second is the design of the phase and amplitude distributions at the image plane so that the diffracted field yields a desired transverse intensity pattern over an extended distance (focal depth). This has been attempted for continuous-phase masks 8 and proven successful only for very simple transverse images.…”
mentioning
confidence: 99%